Floristic composition, structure and tree diversity of an amazon forest in Peru - Alvarez-Montalván, Carlos E. (2021)
The Amazonian forests of Peru are among the most diverse and disturbed by anthropic activities on the planet, today there are still gaps on the composition of the communities and their inter-specific relationships. A forest inventory was carried out in a terraced forest in the Madre de Dios region, 5 blocks were established with 2 rectangular plots of 20m x 500m each to identify and measure individuals with diameter greater than 10 cm. 4429 trees were evaluated and 254 species, 165 genera and 53 families were identified. The distribution of diameter classes and height presents typical patterns of intervened forests, in this case by the extraction of wood decades ago. The average of the biodiversity indices are: Shannon-Wienner 4.039 ± 0.16 and α-Fisher 39.90 ± 9.23, indicating that there is a high diversity of species. The species of greatest ecological importance were: Tetragastris altissima (Aubl.) Swart, Iriartea deltoidea Ruiz & Pav, Euterpe precatoria Mart., Which are fast growing and are present throughout the neo-tropics, Tachigali vasquezii Pipoly, abundant only in the forests of this region; These species took advantage of the opening of the canopy by felling and increased their abundance and dominance in the area. On the other hand, Ocotea bofo Kunth, Bertholletia excelsa Bonpl, Eschweilera coriácea (DC.) S.A. Mori, dominate the forest, but of low abundance, due to changes in the floristic composition after wood harvesting.